NCAPG as a Novel Prognostic Biomarker in Glioma - Jiang, Xiulin; Shi, Yulin; Chen, Xi; Xu, Haitao; Liu, Bohu; Zhou, Fan; Huang, Xiaobin; Cho, William C.; Li, Lihua; Pu, Jun (Frontiers in Oncology, 2022)
Background Non-SMC condensin I complex subunit G (NCAPG) is expressed in various human cancers, including gliomas. However, its biological function in glioma remains unclear. The present study was designed to determine the biological functions of NCAPG in glioma and to evaluate the association of NCAPG expression with glioma progression. Methods Clinical data on patients with glioma were obtained from The Cancer Genome Atlas (TCGA), the Chinese Glioma Genome Atlas (CGGA), the Gene Expression Omnibus (GEO), and the Rembrandt and Gravendeel databases. The correlations among NCAPG expression, pathological characteristics, and clinical outcome were evaluated. In addition, the correlations of NCAPG expression with immune cell infiltration and glioma progression were analyzed. Results NCAPG expression was higher in gliomas than in adjacent normal tissues. Higher expression of NCAPG in gliomas correlated with poorer prognosis, unfavorable histological features, absence of mutations in the isocitrate dehydrogenase gene (IDH), absence of chromosome 1p and 19q deletions, and responses to chemoradiotherapy. Univariate and multivariate Cox analysis demonstrated, in addition to patient age, tumor grade, absence of IDH mutations, and absence of chromosome 1p and 19q deletions, NCAPG expression was independently prognostic of overall survival, disease-free survival, and progression-free survival in patients with glioma. In addition, high expression of NCAPG correlated with tumor infiltration of B cells, CD4+ T cells, CD8+ T cells, neutrophils, macrophages, and dendritic cells. Gene set enrichment analysis (GSEA) indicated that high NCAPG expression was associated with cell proliferation and immune response-related signaling pathways. NCAPG knockdown in glioma cell lines significantly reduced cell survival, proliferation, and migration. Conclusion NCAPG expression correlates with glioma progression and immune cell infiltration, suggesting that NCAPG expression may be a useful prognostic biomarker for glioma.